Quality of life of elderly with alzheimer's disease: a comparative study between the patient's and the caregiver's report Calidad de vida del anciano con enfermedad de alzheimer: estudio comparativo de los relatos del paciente y del cuidador Qualidade de vida do idoso com doença de alzheimer: estudo comparativo do relato do paciente e do cuidador - Keika Inouye; Elisete Silva Pedrazzani; Sofia Cristina Iost Pavarini; Cristina Yoshie Toyoda (Universidade de São Paulo, 2010)
This paper aimed to compare the reports of patients and caregivers about how they perceive quality of life (QoL) in general and each of its dimensions in elderly with Alzheimer's Disease (AD). The participants were elderly diagnosed with AD (n=53) attended by the Exceptional Medication Program in a city in the interior of Sao Paulo; and their respective family caregivers. The QoL measures were obtained through the Quality of Life Assessment Scale on Alzheimer's Disease. The results showed statistically significant differences in the "memory" (p<0.05) and "you in general" (p<0.005) dimensions. Regarding the final score, the average in the patient's version was 29.32 points (sd=6.27), against 28.33 points (sd=5.58) in the family version, p>0.100. Although the relative and patient reports were not identical, the results pointed to a high level of consistency among information. Este estudio tuvo como objetivo comparar los relatos del paciente y el del respectivo cuidador familiar sobre la percepción general y de cada dimensión de calidad de vida (CV) del anciano con enfermedad de Alzheimer (EA). Los participantes fueron ancianos diagnosticados con EA (n=53), atendidos por el Programa del Medicamento Excepcional de una ciudad del interior del estado de Sao Paulo, y sus respectivos cuidadores familiares. Las medidas de CV fueron obtenidas por medio de la Escala de Evaluación de Calidad de Vida en la Enfermedad de Alzheimer. Los resultados mostraron que apenas las dimensiones "memoria" (p<0,05) y "usted en general" (p<0,005) presentaron disparidades estadísticamente significativas. En cuanto al puntaje final, el promedio en la versión del paciente fue de 29,32 puntos (de=6,27) y en la versión del familiar fue de 28,33 puntos (de=5,58), p>0,100. A pesar de que los relatos del familiar y del paciente no son idénticos, los resultados apuntaron una elevada consistencia entre las informaciones. Este estudo teve como objetivo comparar o relato do paciente e do respectivo cuidador familiar sobre a percepção geral e de cada dimensão de qualidade de vida (QV) do idoso com doença de Alzheimer (DA). Os participantes foram idosos diagnosticados com DA (n=53), atendidos pelo Programa do Medicamento Excepcional de uma cidade do interior paulista, e seus respectivos cuidadores familiares. As medidas de QV foram obtidas por meio da Escala de Avaliação da Qualidade de Vida na Doença de Alzheimer. Os resultados mostraram que apenas as dimensões "memória" (p<0,05) e "você em geral" (p<0,005) apresentaram disparidades estatisticamente significantes. Quanto ao escore final, a média na versão do paciente foi de 29,32 pontos (dp=6,27) e na versão do familiar foi de 28,33 pontos (dp=5,58), p>0,100. Embora os relatos do familiar e paciente não sejam idênticos, os resultados apontaram elevada consistência entre as informações.